Phylogenetic analyses of Chinese Tuber species that resemble T. borchii reveal the existence of the new species T. hubeiense and T. wumengense. (1st March 2016) - Fan, Li; Zhang, Peng-rui; Yan, Xiang-yuan; Li, Yu
Abstract : In phylogenetic analyses based on the internal transcribed spacers and 28S nuc rDNA and translation elongation factor 1-α to compare Chinese white truffle specimens that have ascomata resembling the European Tuber borchii, the sequences of Chinese species resembling T. borchii in morphology grouped into seven distinct clusters among three clades: Puberulum, Maculatum and Latisporum . No sequences from these Chinese species matched those of the European T. borchii and the occurrence of the European T. borchii in China could not be supported by our study. Three unknown species are recognized from the seven Chinese clusters; two are described here as T. hubeiense and T. wumengense based on molecular and morphological evidence.